2023
DOI: 10.1007/s42399-023-01622-w
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of Sleep Disorders, Mental Illness, and Migraine or Headaches

Ray M. Merrill,
Ian S. Gibbons

Abstract: This study assesses the comorbidity of mental illness, sleep disorders, and migraine/headaches among employees in a large organization in the USA. The comorbidity of migraine/headaches and sleep disorders or mental illness has been well studied. However, simultaneous comorbidity of all three is less well known. Analyses were based on the Deseret Mutual Benefit Administrator employee database, derived from billing codes for employees and their families during the years 2017–2021. Statistical analyses were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Conversely, a study examining the overlap of mental illness, sleep disorders, and migraines/headaches in a large US organization from 2017 to 2021 revealed that individuals with both sleep and mental disorders, particularly depression and anxiety, are more prone to migraines, with 1.30 and 1.60 increase in the likelihood, respectively. Furthermore, those with only a sleep disorder, only mental illness, or both are respectively 1.33, 1.62, and 2.89 more likely to experience migraines ( Merrill & Gibbons, 2023 ). Given the increased risk of comorbid psychiatric symptoms in migraine patients, it is essential to explore and evaluate the effectiveness of new migraine preventive treatments for those with comorbid anxiety and/or depression ( Jette et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a study examining the overlap of mental illness, sleep disorders, and migraines/headaches in a large US organization from 2017 to 2021 revealed that individuals with both sleep and mental disorders, particularly depression and anxiety, are more prone to migraines, with 1.30 and 1.60 increase in the likelihood, respectively. Furthermore, those with only a sleep disorder, only mental illness, or both are respectively 1.33, 1.62, and 2.89 more likely to experience migraines ( Merrill & Gibbons, 2023 ). Given the increased risk of comorbid psychiatric symptoms in migraine patients, it is essential to explore and evaluate the effectiveness of new migraine preventive treatments for those with comorbid anxiety and/or depression ( Jette et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the cumulative incidence of PTH within 1 year after mTBI is as high as 91% [ 5 , 6 ]. Although PTH may be the only symptom after a head injury, it is often accompanied by other trauma-related symptoms, including sleep problems, posttraumatic stress, imbalance or vertigo, cognitive dysfunction, personality changes, depression, anxiety, and extracranial pain [ 7 9 ]. However, no specific symptoms or headache features have been shown to contribute to the diagnosis of PTH [ 10 ].…”
Section: Introductionmentioning
confidence: 99%